Professional Dialogue as Professional Learning - Anne Grey (New Zealand Journal of Teachers' Work)
This article discusses professional dialogue as an important aspect of professionalism for early childhood teachers. It draws on the experiences of four qualified early childhood teachers of one teaching team in an early childhood centre who engaged in extensive professional dialogue with each other. Dialogue focused on the values that underpinned and were reflected in their teaching practice. These values were discussed in order to explore the commonalities and differences in teaching philosophies amongst the team. The article outlines both the benefits and the challenges of engaging in professional dialogue by drawing on the perceptions of the teachers who participated. The article contends that professional dialogue should be viewed as an alternative form of professional learning.